Baby Halder's A Life Less Ordinary: Domestic Work, Motherhood and the Dalit Woman. Issue 2 (December 2018) - Nath, Arpana
Autobiographical writings by women are a recent addition to the body of scholarship on women's issues in India. Colonial discourse on nationalism created a new ideal of femininity by conflating the maternal with the body of the nation. A few recent studies have tried to focus on the lived experiences of mothers and their contribution to the process of nation building during the nationalist movement. This has been of great help in bringing the figure of the 'mother' out of oblivion towards a new understanding of maternity. Dalit autobiographies by women (or testimonios as they are now called) attest to the pain and trauma of social exclusion and provide a counter discourse to the dominant cultural narrative of maternity in the context of gender ideology, family and work relations. As mothers and women from a marginalized group, they possess little control over the social environment. The life narratives of Dalit women show a strong sense of self and an awareness of the humanizing capacity of education to liberate the subject. Breaking the myth of the good mother, these stories speak of the ambivalence and pain of their own maternity, their struggle to take control of their lives and the empowerment of their children through education. This article is an attempt to read Baby Halder's A Life Less Ordinary (translated by Urvashi Butalia, 2006) in the light of the above assumptions.